(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This article analyzes the process of treating patients with CHF and CHF with a low ejection fraction against the background of type 2 diabetes mellitus. Approximately 1-2% of the adult population of developed countries have heart failure (HF), in patients over the age of 70, the risk of developing HF is more than 10%. In 2016, a new drug appeared in the arsenal of cardiologists — sacubitril/valsartan (Uperio), which is a complex of a non-lysine inhibitor and an angiotensin-2 receptor blocker. The study was randomized - 27 reviewers hospitalized for the period February – March 2022: 21 / (78%) men, and 6 / (22%) women. By week 10, 17 / (63%) patients received the target dose of the drug - Uperio, by week 18 – 20 / (74%) (Table No. 2). In two patients, the titration of the dose of the drug - Uperio was not carried out due to the development of symptomatic arterial hypotension. Nine patients by week 20 received a dose of 100 mg 2 times a day of the drug - Uperio. 5 of them had a decrease in eGFR. Patients showed improvements in the clinical picture, an increase in the functional class according to NYHA, improvements in laboratory data (decrease in creatinine levels, decrease in NT-proBNP levels), as well as positive dynamics on EchoCG.